Peran Edupreneurship dalam Meningkatkan Kualitas Kemandirian Berwirausaha Santri Pondok Pesantren Nurul Ummah Kotagede Yogyakarta - Syakur Wildan; Subiyantoro Subiyantoro (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
Edupreneurship is a renewal innovation, especially in the field of education so as not to make a large quantity without good achievements. However, it can produce qualified, qualified, and highly competitive graduates to make positive and beneficial contributions to many people. Edupreneurship is also the answer to the problems currently being faced by the Indonesian people. It can create superior, creative, independent, innovative human resources (HR), and have an entrepreneurial mentality so that unemployment and economic backwardness can be minimized. An entrepreneur who is often referred to as an entrepreneur is someone who wants to develop creative skills, create works, has a visionary spirit, has self-reliance, and dares to take risks. This research method uses qualitative research with a case study approach to the students of the Nurul Ummah Islamic Boarding School. This study aims to provide opportunities for students in developing their potential in the field of entrepreneurship so that they can be developed to the maximum. The results of the study indicate that edupreneurship is a renewal innovation, especially in the field of education so as not to make a large quantity without good achievements. However, it can produce qualified, qualified, and highly competitive graduates to make positive and beneficial contributions to many people.